2023
DOI: 10.3390/v15030673
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter Baumannii Phages: Past, Present and Future

Abstract: Acinetobacter baumannii (A. baumannii) is one of the most common clinical pathogens and a typical multi-drug resistant (MDR) bacterium. With the increase of drug-resistant A. baumannii infections, it is urgent to find some new treatment strategies, such as phage therapy. In this paper, we described the different drug resistances of A. baumannii and some basic properties of A. baumannii phages, analyzed the interaction between phages and their hosts, and focused on A. baumannii phage therapies. Finally, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 237 publications
0
8
0
Order By: Relevance
“…A. baumannii is currently considered a pathogenic bacterium of clinical relevance, mainly due to the emergence of strains resistant to multiple drugs and associated with infections related to health care [Tu et al, 2023;Wu et al, 2023]. In this scenario, the study of genes that encode virulence factors and confer resistance to antimicrobials is of paramount importance for a better understanding of the pathogenicity of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…A. baumannii is currently considered a pathogenic bacterium of clinical relevance, mainly due to the emergence of strains resistant to multiple drugs and associated with infections related to health care [Tu et al, 2023;Wu et al, 2023]. In this scenario, the study of genes that encode virulence factors and confer resistance to antimicrobials is of paramount importance for a better understanding of the pathogenicity of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Phage therapy is currently one of the best hopes for the future control of Gram-negative severe infections that are difficult to eradicate with antibiotics [189 ▪ –192 ▪ ]. This form of treatment first requires the availability of phages with lytic capacity for a specific bacterium, in this case, AB, of which more than 100 have been isolated to date [193,194 ▪ –201 ▪ ].…”
Section: What Are the Alternative Treatments For Acinetobacter Bauman...mentioning
confidence: 99%
“…New or alternative management methods are needed. Phages are abundant in the environment, and they can specifically attack pathogenic bacteria (Tu et al, 2023 ). Phages may be found that can attack Multidrug-Resistant (MDR) strains of A. baumannii which may be a potential solution for this pathogen (Tu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%